Rancang Bangun Sistem Informasi Perpustakaan Pada SDN 21 Desa Sesap - Ahai Ahai (Mahesa Research Institute, 2023)
With the rapid development of information technology, it has a very important role in various fields, one of which is education. The library information system is a system that is very useful for managing, making things easier for staff and storing library book collections using the system. SD Negeri 21 Sesap Village has a library that stores various kinds of learning books, but the service is still done manually or still in the form of bookkeeping, so it is prone to errors, for example library member data, book data and borrower data. In this research, interview and literature study methods were used, and the programming language used was Hypertext Processor (PHP) and the database used MySQL. The aim of this paper is to design a computerized library information system at SD Negeri 21 Sesap Village to make it easier to manage book data and anticipate errors that occur in library management at SD Negeri 21 Sesap Village.